PERMODELAN MUKA AIRTANAH BEBAS DAERAH JAKARTA DAN SEKITARNYA - RUNTIARKO
Groundwater is one of the important water resources for the people in Jakarta, more than 40% they used phreatic water. In managing and developing of phreatic groundwater utilization, knowledge about lateral and horizontal spreading of groundwater is needed. One of the method to Know the spreading of phreatic groundwater in discribing the height of phreatic water level is by making the contour lines. In this paper discussed a method of estimating the shape of phreatic water level in the vicinity of Jakarta by using a mathematical model as a developing of Darcy law and Continuitas law, by finite difference analysis. The model can be used to estimate the shape of water level contour or the make forecasting the behaviour of phreatic water in the Jakarta for future.